Creative city, mobility, and creativity: Finnish artists in Berlin - Johanna Hautala; Paulina Nordström (Taylor & Francis, 2022)
Creative city, creativity, and mobility are interconnected. The creative city research focuses on long-term mobility of the creative class members: they ‘move in’ to a creative city. ‘Once in’ the creative city, the city is seen to (automatically) support the creativity of the individuals. However, artists and other creative class members constantly visit and work temporarily in creative cities. Moreover, the creation processes of individuals in the creative cities are less known. We focus on mobilities along the process of creation from ‘creative moments’ to ‘creative outcomes’. We investigate Finnish artists in Berlin to analyse how the artists use mobilities (‘move in’, ‘once in’ and ‘once out’) to support their creative process. We apply interviews of 16 Finnish artists in 2014 − 2015 and a survey one year later. The results demonstrate visitor, transnational, and migrant mobilities, each with particular support for the creation process and with different geographies of mobilities. We contribute to the research on creative cities by elaborating the interrelatedness of creativity, mobility, and a creative city. According to the results, creative cities are not the only important sites for creation processes. Creative moments experienced in creative cities may be turned into creative outcomes elsewhere.